P2_5 Heating in rim-brakes - Weaver, Iain; Anand, Jasdeep; Gorley, Michael; Buccheri, Alex (Physics Special Topics, 2009)
<span style="font-size: 10pt; font-family: ";Calibri";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">It has been reported that rim-brakes on bicycles can heat the rim sufficiently to blow the tyre off the rim. This paper investigates the magnitude of heating caused by rim-brakes, and determines the effect of this heating on tyre pressure. It is found that rim-heating appears to significantly increase pressure by up to 30%, though there is no experimental data to fit the model to for a more rigorous conclusion.